2006
DOI: 10.1111/j.1349-7006.2006.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of carcinogenic potential by a toxicogenomic approach using rat hepatoma cells

Abstract: The long-term rodent bioassay is the standard method to predict the carcinogenic hazard of chemicals for humans. However, this assay is costly, and the results take at least two years to produce. In the present study, we conducted gene expression profiling of cultured cells exposed to carcinogenic chemicals with the aim of providing a basis for rapid and reliable prediction of carcinogenicity using microarray technology. We selected 39 chemicals, including 17 rat hepatocarcinogens and eight compounds demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…(B) Test chemicals that were correctly predicted positive by the signature (beta-napthoflavone, DES, chloroform, DEHP) clustered most closely to the representative reference compounds with similar MOA. Kramer et al, 2004;Tsujimura et al, 2006), more extensive independent validation is needed to increase the confidence in their general utility. Likewise, other attempts using larger data sets (Nie et al, 2006) show promise and await further independent validation.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Test chemicals that were correctly predicted positive by the signature (beta-napthoflavone, DES, chloroform, DEHP) clustered most closely to the representative reference compounds with similar MOA. Kramer et al, 2004;Tsujimura et al, 2006), more extensive independent validation is needed to increase the confidence in their general utility. Likewise, other attempts using larger data sets (Nie et al, 2006) show promise and await further independent validation.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicogenomics (mRNA transcript profiling) to identify genes that respond to groups or categories of chemicals and statistical classification methods together with machine learning [Auerbach et al, 2010] clearly have progressed in their ability to predict carcinogenicity. Recent studies reviewed in Waters et al [in press] by Van Delft et al [2004, 2005], Ellinger-Ziegelbauer et al [2005, 2008, 2009a], Nakayama et al [2006], Nie et al [2006], Tsujimura et al [2006], Fielden et al [2007, 2008], Thomas et al [2007] suggest that it is possible to screen for carcinogenicity and to discern the potential mode of action (MOA) of a chemical based on analysis of gene expression using toxicogenomics methods, with the potential for screening of putative MOA by quantitative RT-PCR [Ellinger-Ziegelbauer et al, 2009b]. The strategy used involves selecting a training set of known carcinogenic (genotoxic or nongenotoxic) and non-carcinogenic compounds to which to expose mice or rats in vivo or cultured cells in vitro for periods of from 1 to 90 days.…”
Section: Toxicogenomicsmentioning
confidence: 99%
“…Alternative tests are therefore required. The application of transcriptomics approaches to detect carcinogenic features of chemicals has been extensively investigated in vivo as well as in vitro (EllingerZiegelbauer et al 2009a;Fielden et al 2011;Thomas et al 2009;Tsujimura et al 2006;Yamada et al 2012). Overall, these studies have yielded biologically relevant gene signatures, which can be employed to distinguish different chemical classes, e.g, (non-) genotoxic carcinogens versus noncarcinogens (Ellinger-Ziegelbauer et al 2008;Melis et al 2014; Thomas et al 2009;Watanabe et al 2012;Yamada et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In vitro systems in which toxicogenomics has been explored for assessment of the carcinogenic features of substances are, just like in vivo, mainly of hepatic origin: (primary) hepatocytes or hepatic (cancer-) cell lines (e.g., HepG2, MH1C1) (Ellinger-Ziegelbauer et al 2009b;Magkoufopoulou et al 2012;Mathijs et al 2009;Tsujimura et al 2006). The results of these studies indicated that toxicogenomicsbased in vitro assays are promising tools to detect mainly genotoxic carcinogens.…”
Section: Introductionmentioning
confidence: 99%